Revenge Porn: Digital Crimes and Implications for Victims - Zico Junius Fernando; Papontee Teeraphan; Jaco Barkhuizen; Agusalim Agusalim (Universitas Muhammadiyah Purwokerto, 2023)
In today's digital era, problems related to cybercrime are increasing, one of which is